Payment and Coverage Parity for Virtual Care and In-Person Care: How Do We Get There? - Nandita Khera; Meghan Knoedler; Sarah K. Meier; Sarvam TerKonda; Ryan D. Williams; Christopher M. Wittich; Jordan D. Coffey; Bart M. Demaerschalk (Telemedicine Reports, 2023)
Background: A steep increase in the use of delivery of virtual care occurred during the COVID-19 public health emergency (PHE) because of easing up of payment and coverage restrictions. With the end of PHE, there is uncertainty regarding continued coverage and payment parity for the virtual care services. Methods: On November 8, 2022, The Mass General Brigham held the Third Annual Virtual Care Symposium: Demystifying Clinical Appropriateness in Virtual Care and What's Ahead for Pay Parity. Results: In one of the panels, experts from Mayo Clinic led by Dr. Bart Demaerschalk discussed key issues related to ?Payment and Coverage Parity for Virtual Care and In-Person Care: How Do We Get There?? The discussions centered around current policies around payment and coverage parity for virtual care, including state licensure laws for virtual care delivery and the current evidence base regarding outcomes, costs, and resource utilization associated with virtual care. The panel discussion ended with highlighting next steps targeting policymakers, payers, and industry groups to help strengthen the case for parity. Conclusions: To ensure the continued viability of virtual care delivery, legislators and insurers must address the coverage and payment parity between telehealth and in-person visits. This will require a renewed focus on research on clinical appropriateness, parity, equity and access, and economics of virtual care.